Literary History Meets the History of Reading: The Case of La Princesse de Clèves and Its (Non)readers. - TURNOVSKY, GEOFFREY (French Historical Studies, 2018)
This article revisits the letters written by readers of the Mercure galant who responded to the "gallant question," posed by the periodical's editor in an April 1678 issue, regarding a central plot twist of Madame de Lafayette's novel La Princesse de Clèves. Highlighting the expansive, democratic, and participatory nature of this readership that connected with the unprecedented complexity of the novel's characters, scholars have imputed to this public a modernity reflecting that of the novel itself, often considered "the first modern novel" in French. Closely analyzing the letters in light of their arguments and of the novel's editorial history, this essay explores the implications of a disconnect between the work and the readers in question, who had perhaps not read the text and did not, in any case, empathize with its protagonist's dilemma as presented by the Mercure.